A History of Da'wah among Non-Muslims Through the Ages | تاريخ دعوة غير المسلمين عبر العصور - Ghilmanul Wasath (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2018)
This study discusses a history of da'wah aimed at non-Muslims, which has been carried out since the time of the Prophet until today. The involvement of Muslim rulers and scholars has paved the way for geographical expansion and the expansion of Islamic thought. The results of this study reinforce that jihad is the foundation for upholding religion and reforming human beings on the earth. In the history of Da'wah among non-Muslims, various approaches to da'wah ranging from correspondence, teaching, inter-religious dialogue, treaties to conquests were synergized in the thought of faith in Allah and the the Hereafter, the adherence of the ummah to religious messages, and the movement of rulers and scholars in the path of da'wah.